2021
DOI: 10.2174/1871526520999200917152502
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of OXA-type Class D β-lactamases Among Clinical Isolates of Klebsiella Pneumoniae in Multiple Centers of Tehran, Iran

Abstract: Background: Drug- and multidrug-resistant Klebsiella pneumoniae isolates have been found worldwide. Treatment failures against carbapenems and extended-spectrum cephalosporins, the currently recommended drugs, contribute to consider K. pneumoniae infections as untreatable infections. The emergence and spread of oxacillinases (OXAs) with carbapenem-hydrolysing properties are a major concern and seriously become a public health problem worldwide. The present study was aimed to explore the blaOXA genes among clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Multidrug-resistant bacteria (MDR) infections, featuring high incidence and fatality rates, are a threat to public health ( Liu et al, 2020 ; Yu et al, 2020 ; Mei et al, 2021 ). Among them, carbapenem-resistant Klebsiella pneumoniae (CRKP) has been listed as one of the most critical drug-resistant pathogens by the World Health Organization, because its carbapenemases product, capable of hydrolyzing and inactivating carbapenems and β-lactams antibiotics, can result in the dramatical infection occlusion in bloodstream, urinary tract, surgical-site, and lung ( Broberg et al, 2014 ; Escolà-Vergé et al, 2020 ; Mehrbakhsh et al, 2020 ; Han et al, 2022 ; Liu et al, 2022 ). To treat the bacterial infections, extensive efforts have been devoted and remarkable progresses have been made using various antibiotics ( Ji et al, 2021 ; Zong et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Multidrug-resistant bacteria (MDR) infections, featuring high incidence and fatality rates, are a threat to public health ( Liu et al, 2020 ; Yu et al, 2020 ; Mei et al, 2021 ). Among them, carbapenem-resistant Klebsiella pneumoniae (CRKP) has been listed as one of the most critical drug-resistant pathogens by the World Health Organization, because its carbapenemases product, capable of hydrolyzing and inactivating carbapenems and β-lactams antibiotics, can result in the dramatical infection occlusion in bloodstream, urinary tract, surgical-site, and lung ( Broberg et al, 2014 ; Escolà-Vergé et al, 2020 ; Mehrbakhsh et al, 2020 ; Han et al, 2022 ; Liu et al, 2022 ). To treat the bacterial infections, extensive efforts have been devoted and remarkable progresses have been made using various antibiotics ( Ji et al, 2021 ; Zong et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular studies displayed a frequent distribution of blaOXA including blaOXA-1 , blaOXA-2 , blaOXA-48 etc. among K. pneumoniae [ 9 ]. Among the blaOXA-48 -like CHβLs group, blaOXA-48 , blaOXA-181 , blaOXA-232 , blaOXA-204 , blaOXA-162 , and blaOXA-244 are the most common enzymes identified, and some of them showed an epidemic state, for example, it has been reported that blaOXA-48 is endemic in Europe and Asia [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…ESBLs are commonly detected in strains of Klebsiella pneumoniae, qualified as an opportunistic pathogen, the etiologic agent of serious infections in hospitalized patients, with emphasis on patients with compromised immunity to serious diseases. K. pneumoniae capable of producing β-lactamase was first detected in Germany in 1983, and there has been a steady increase worldwide in subsequent decades [1,2]. Nosocomial infections are usually caused by K. pneumoniae, Acinetobacter baumanie, and other gram-negative microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…The biggest problem is that the pharmaceutical industry does not have enough new drugs to complement the growth of resistance of these microorganisms, such as K. pneumoniae . The growing number of cases of antibiotic-resistant Klebsiella pneumoniae infections stands out as a worldwide health problem, presenting as a clinically important bacterium causing pneumonia in hospital environments [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation